2017
DOI: 10.3928/02793695-20170818-04
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a Workplace Violence Simulation for Undergraduate Nursing Students: A Pilot Study

Abstract: Workplace violence (WPV) is an undesired phenomenon affecting nurses and nursing students. Nursing simulations allow students to learn and practice skills in a controlled setting. The development of the pilot study, "Mental Health Nursing Simulation on Workplace Violence," is presented. A simulated scenario using a standardized patient (SP) behaving as an agitated psychiatric patient was developed for undergraduate nursing students enrolled in a psychiatric nursing course. The simulation aimed to enhance stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(83 citation statements)
references
References 16 publications
1
76
0
6
Order By: Relevance
“…Using simulation resources, researchers addressed different topics of violence, such as patient violence, assault, shooter presence at the workplace, horizontal violence (among nurses), bullying and violence management. (13,14,(27)(28)(29)(30)(31)(32)(33) Patient-generated events were the main topic of violence addressed in the studies (Chart 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using simulation resources, researchers addressed different topics of violence, such as patient violence, assault, shooter presence at the workplace, horizontal violence (among nurses), bullying and violence management. (13,14,(27)(28)(29)(30)(31)(32)(33) Patient-generated events were the main topic of violence addressed in the studies (Chart 2).…”
Section: Resultsmentioning
confidence: 99%
“…The six papers indicated some benefit of the simulation, but there were neutral or less favorable results even after implementation. (13,14,(27)(28)(29)33) Category II was composed of three studies that showed SE III and that involved nursing students, workers (including nurses) and mentors. In this case, data measurement was performed during or after intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Caring for numerous aggressive or agitated patients adds to the daily stress of a nursing student and may lead to disengagement (Martinez, 2017;Tee et al, 2016). When the staff fail to report incidents (Martinez, 2016) and inadvertently allow the violence to continue, the belief that nursing the sick and infirm means suffering abuse is internalized as part of the job (Brann & Hartley, 2017).…”
Section: Recommendationsmentioning
confidence: 99%
“…Agitated-patient scenarios should be worked into multiple course simulations (Martinez, 2017) and case study practice just as medical complications are instilled. In this way, scenarios with a medical basis will be more realistic, and true to current patient populations.…”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation